The relationship between ethmoid roof and cribriform plate dimensions and degree of septal deviation angle by computerized tomography - Ahmed S.A Elgalil; Mahmoud I Elshamy; Mohammed A.E Yonis; Ibrahim M Eldiehy (Wolters Kluwer Medknow Publications, 2020)
Background Endoscopic sinus surgery (ESS) is a common operation for the management of sinonasal pathologies. The surgeons dealing with ESS should understand the crucial complex anatomy of the anterior cranial base to avoid the intracranial violation during ESS. Objective The aim of this work was to investigate the relationship between degree of septal deviation angle and the dimensions of cribriform plate (CP) and ethmoid roof by evaluation of the paranasal computed tomography. Patients and methods A total of 40 patients, comprising 20 females and 20 males, with age ranging from 18 to 60 years, were selected according to inclusion and exclusion criteria from the outpatient ENT clinics of El-Hussein and Bab-El-She'reya Hospitals from November 2017 to January 2019. Results The severity of deviation did not affect the dimensions of the ethmoid roof and CP in terms of depth and width, except right ethmoid roof width (direct proportion) and the left cribriform width (inverse proportion). There was a significant direct relationship between ipsilateral and contralateral ethmoid roof (ER) width and between ipsilateral and contralateral ER depth. This study showed no significant relation between ipsilateral and contralateral CP width. High rate of asymmetry between CP and ethmoid roof in this study (100%) was noted. Conclusion In cases of deviated nasal septum, the increase in the severity of septum deviation raises the possibility of the increasing right ethmoid roof width and of decreasing the left cribriform width, and this possibility should be taken into consideration to avoid iatrogenic injury during ESS.